Lipid residue analysis reveals divergent culinary practices in Japan and Korea at the dawn of intensive agriculture - Oliver E. Craig; Jasmine Lundy; Manon Bondetti; Sesha Nicholson-Lailey; Natsuki Murakami; Miho Suzuki; Chris Stevens; Alexandre Lucquin; Helen M. Talbot; Joon-ho Son; Shinichiro Fujio; Minoru Sakamoto; et al. (Proceedings of the National Academy of Sciences, 2025)
The dispersal of millet and rice agriculture from Korea to Japan from around 3,000 y ago has been well documented through radiocarbon analysis of botanical remains and surveying seed impressions on pottery. Much less is known about the extent to which these novel crops were consumed and incorporated into everyday culinary practices. In Japan, agriculturalists moving from Korea would have encountered large, sedentary Final Jomon populations who had well-established hunting, foraging, and cultivation strategies for exploiting indigenous fauna and flora. The degree to which these encounters hindered or enhanced the emergence of agriculture is a key question. To investigate potential changes in food exploitation, we analyzed the contents of pottery through lipid residue analysis of 260 vessels from Bronze Age (Mumun) Korea and contemporary Jomon and Yayoi pottery from Northern Kyushu. A lipid biomarker for broomcorn millet was only found in samples from Korea, suggesting that this crop was not routinely prepared in early agricultural pottery from Japan, despite some botanical evidence for its cultivation. Instead, aquatic products continued to be used in early agricultural pottery, pointing to continuity from the Jomon period despite the arrival of new “continental” ceramic forms. Rice remains difficult to identify conclusively, but by modeling carbon isotope values, we were able to determine the maximum extent that rice may have contributed. Overall, we show that there was a change in culinary practices as agriculture dispersed from Korea to Japan, most likely influenced by different long-standing traditions of preparing and cooking foods in each locality.